Kesiapan SDM UMKM Dalam Menghadapi Era Industri 4.0 - Rokhmawati, Dian (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
Abstract. Industry 4.0 has a tremendous impact on many aspects of life. Technological aspects, social aspects, legal and political aspects, environmental aspects, and economic aspects. MSME’s readiness as a support of the national economy to respond to the challenges that follow is interesting to study. Human resources are the most valuable assets in the economy structure. So that the management and qualifications of human resources become very important to know, as changes are caused by industry 4.0. This study aims to determine the competency component of Human Resources and determine the human resources readiness of MSME’s in facing the Industry 4.0. This research uses literature study to find out the competency component of human resources needed in industry 4.0 then it is used gap analysis to describe the human resources readiness of MSME in facing Industrial Revolution 4.0. From the results of this study indicate that the average score for the variable technical competence is 2.4, methodological competence is 2.97, social competence is 2.85, personal competence is 3.25. The average score is 2.86. So it can be concluded that the human resources readiness of MSMEs in facing Industrial Revolution 4.0 in the Not Ready category, (need some of work) Index 2.6 - 3.39. Keywords: Readiness; Human Resources; MSME’s; Industry 4.0 Abstrak. Revolusii Industrii 4.0i membawa dampak iluar biasai pada banyak aspek idalam kehidupan. Aspek teknologi, aspek sosial, aspek hukum dan politik, aspek lingkungan, serta aspek ekonomi. Kesiapan UMKM sebagai penopang perekonomian nasional untuk menjawab tantangan-tantangan yang mengikutinya menjadi menarik untuk diteliti. Sumber Daya Manusia adalah aset paling bernilai dalam struktur perekonomian. Sehingga pengelolaan dan kesiapan akan kualifikasi iSumber iDaya iManusia imenjadi ihal iyang isangat ipenting untuk ketahui. Penelitiani inii bertujuan untuk mengetahui komponen kompetensi Sumber Daya Manusia dan mengetahui kesiapan SDM UMKM idalam imenghadapi iRevolusi iIndustri i4.0. Penelitan ini menggunakan studi literatur untuk mengetahui komponen kompetensi SDM kemudian digunakan gap analisis untuk mendeskripsikan kesiapan SDM UMKM dalam menghadapi Revolusi iIndustri i4.0. Dari ihasil ipenelitian iini menunjukkan bahwa skor rata-rata untuk variabel kompetensi teknikal adalah 2,4, kompetensi metodologis adalah 2,97, kompetensi sosial adalah 2,85, kompetensi personal adalah 3,25. Nilai rata-rata skor 2,86. Sehingga dapat disimpulkan bahwa kesiapan SDM UMKM idalam imenghadapi Revolusi iIndustri 4.0 idalam ikategori Not Ready, (need some of work) Indeks 2,6 – 3,39. Kata Kunci: Kesiapan; iSumber iDaya iManusia; UMKM; iRevolusi iIndustri 4.0i